Effectiveness of Face Recognition-Based Security System on CCTV with Raspberry Pi and Esp32-Cam Using Face Recognition Method - Frencis Matheos Sarimole; Satria Wira Yudha; Sutisna Sutisna; Ahas Eko Septianto (Journal of Engineering, Electrical and Informatics, 2022)
Current technological advances, such as the internet of things (IOT), have a very broad scope. Especially in the security sector. The fact is that there are many robots that have been made by humans to do jobs that can help humans beyond their abilities. CCTV is very important to protect the house from various types of threats, such as burglary and other hazards. However, a security system that only uses CCTV cameras is no longer secure enough because someone is needed to monitor activities in the CCTV area for 24 hours. As for CCTV that provides facial recognition features, the price is arguably quite expensive. Therefore, we need home security with a more modern, affordable, and effective version of CCTV that utilizes the technology that has been developed to date. In this context, I propose a prototype of a sophisticated, low-cost, Raspberry-PI-based home security system that is integrated with a mobile real-time application. This intelligent robot can monitor the surrounding area by detecting people who are within the range of the camera. notification if a stranger enters the area and is not recognized by the robot to a mobile application that can be installed. The author uses Raspberry Pi hardware as the main control center, OpenCV to perform motion detection and facial recognition, a webserver to make it easier for users to access data and control the system remotely, mobile applications as notification recipients, and real-time monitoring of CCTV. In the tests carried out, the developed IOT-based security system has succeeded in detecting motion and facial recognition with good accuracy and is able to send notifications to smart phones in a short time when suspicious events occur in the house. Thus, this IOT-based home security system can help improve security and comfort by integrating technology and providing more effective and efficient solutions for protecting homes and buildings from various types of threats